Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1177/106002809703101108
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen Toxicity in Patients with Severely Impaired Renal Function

Abstract: Patients with severely impaired renal function generally develop baclofen intoxication soon after the initiation of low-dose therapy. Thus, the administration of baclofen, regardless of the dosage, in these patients is not appropriate. Abdominal pain, in addition to altered consciousness, is a common presenting feature in patients with renal failure who have baclofen intoxication. Hemodialysis is effective in alleviating the clinical symptoms and shortening the recovery time for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 22 publications
1
65
0
1
Order By: Relevance
“…The elimination half-life of baclofen is 2–6 h for therapeutic oral doses in healthy volunteers and elderly patients [4,5], but half-life increases with renal insufficiency [6,7,8,9,10]. Baclofen has a limited hepatic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination half-life of baclofen is 2–6 h for therapeutic oral doses in healthy volunteers and elderly patients [4,5], but half-life increases with renal insufficiency [6,7,8,9,10]. Baclofen has a limited hepatic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a significant reduction in the daily dose is mandatory in patients with renal insufficiency. Most nephrologists consider baclofen to be a drug that should not be used in patients with end-stage renal disease (ESRD) [7,8,11]. …”
Section: Introductionmentioning
confidence: 99%
“…The appropriate serum level of baclofen in patients with severely impaired renal function remains unclear. Chen et al have thought that patients with renal failure are more susceptible to baclofen toxicity [2]. Similarly our patient had toxicity with a low-dose (50 mg).…”
Section: Discussionmentioning
confidence: 79%
“…Baclofen is eliminated predominantly by the kidneys and patients with impaired renal function have particular risk for baclofen accumulation [1]. Some authors have suggested that haemodialysis is effective in the removal of baclofen, however the pharmakokinetics of baclofen elimination during haemodialysis remains unclear [2]. In this article we report a baclofen intoxication in a patient with chronic renal failure, which was resolved by haemodialysis.…”
Section: Introductionmentioning
confidence: 88%
“…Son dönem böbrek yetersizliği olan hastalarda baklofen birikimi olduğu ve yarılanma ömrünün uzadığı belirtilmektedir (19). Yapılan birçok çalışmada renal yetersizliği olan ciddi baklofen toksisite olgularında hemodiyaliz uygulamaları ile serum baklofen kosantrasyonun hızla düştüğü, baklofen yarılanma ömrünün kısaldığı ve klinik semptomların hızla iyileştiği gösterilmiştir (20)(21)(22)(23)(24). Kısıtlı sayıda çalışmada ise normal renal fonksiyonu olan baklofen entoksikasyonu olgularında da hemodiyaliz ile yine aynı faydaların sağlandığı belirtilmektedir (25,26).…”
Section: Discussionunclassified